QTL-Seq and Transcriptome Analysis Disclose Major QTL and Candidate Genes Controlling Leaf Size in Sesame (Sesamum indicum L.) - Sheng, Chen; Song, Shengnan; Zhou, Rong; Li, Donghua; Gao, Yuan; Cui, Xianghua; Tang, Xuehui; Zhang, Yanxin; Tu, Jinxing; Zhang, Xiurong; Wang, Linhai (Frontiers in Plant Science, 2021)
Leaf size is a crucial component of sesame (Sesamum indium L.) plant architecture and further influences yield potential, as leaves are the principal photosynthetic organs of plants. Despite it is well known that leaf size traits are quantitative traits controlled by large numbers of genes, quantitative trait loci (QTL) and candidate genes for sesame leaf size remain poorly understood. In the present study, we combined QTL-seq approach and SSR marker mapping to identify the candidate genomic regions harboring QTL controlling leaf size traits in a RIL population derived from a cross between sesame varieties Zhongzhi No.13 (big leaves) and ZZM2289 (small leaves). Finally, a total of 56 QTL for the length and the width of leaves at 1/3 and 1/2 position of plant height were detected using 942 developed SSR markers, with phenotypic variation explained (PVE) from 1.87% to 27.50%. qSL15-1, a major and environmentally stable pleiotropic locus for both leaf length and width explaining 13.82% phenotypic variation in average, was located on LG15 within a 408Kb physical genomic region flanked by the markers ZMM6185 and ZMM6206. In this region, a combination of transcriptome analysis with gene annotations revealed three candidate genes SIN_1004875, SIN_1004882 and SIN_1004883 associated with leaf growth and development in sesame. These findings provided insight into the genetic characteristics and variability for sesame leaf, and set up the foundation for future genomics studies on sesame leaves and will serve as gene resources for improvement of sesame plant architecture.